Pengaruh Modal Usaha, Jam Kerja Dan Lama Usaha Terhadap Pendapatan UMKM Di Kecamatan Ngunut - Riski Wulandari; Hari Subiyantoro (Journal of Creative Student Research, 2023)
. The purpose of this study was to determine partially the effect of working hours and length of business capital on business income and to determine simultaneously the effect of working hours and business length of business capital on business income. This study uses a quantitative approach, in that the data collected in research activities is presented in the form of numbers and the analysis uses statistics. The number of samples is 70 SMEs in the district of Ngunut. The results of this study indicate that: partially, there is a significant influence of business capital on MSME income in Ngunut District, with a t count = 5.539 > t table = 1.668 and sig = 0.000 <0.05. Partially, there is a significant effect work on MSME income in Ngunut District, with tcount = 2.876 > ttable = 1.668 and sig = 0.004 <0.05. Partially, there is a significant effect between the length of business on MSME income in Ngunut District, with a tcount = 3.514> t table value of 1.668 and sig = 0.001 <0.05. Simultaneously there is a significant effect between business capital, working hours and length of business on MSME income in Ngunut District, with a Fcount value greater than Ftable (29.493> 2.74) and a significance value less than 0.05 (0.000 <0.05).